2018
DOI: 10.1155/2018/1293273
|View full text |Cite
|
Sign up to set email alerts
|

Design and Efficiency Research of a New Composite Vibrating Screen

Abstract: A new composite vibrating mode is presented in this paper. Modeling and dynamic analysis are studied according to two-degree-of-freedom systems theory. The effects of vibration parameters, including swing angle, swing frequency, vibrating direction angle, and translation frequency, on the screening efficiency were researched by means of experiment research over a new laboratory-scale composite vibrating screen which is designed based on the new composite vibrating mode. The results are analysed in terms of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Pada kajian desain dan rekayasa mesin classifier menggunakan dua metode, yaitu pemodelan menggunakan software SolidWorks 2019 dan metode Finite Element Analysis (FEA) pada screen mesh, mesin menggunakan static analysis pada software ANSYS 2022 [6][7][8][9]. Kajian ini terdiri dari 3 tahapan yang dijelaskan sebagai berikut.…”
Section: Metodeunclassified